ANALISIS KINERJA KARYAWAN DI THE VILLAS BALI HOTEL AND SPA KUTA, BADUNG - Ayu Sriathi, A.A. (PIRAMIDA; Vol. 5, No.2 Desember 2009, 2012)
Improvement the performance of employee is give positive impact incorporate goal, therefore management has to learn attitude and behaviouremployee in corporate. There are some factor which influence for performancean employee, amongst those level stress of employee and industrial'srelationship. Thing such it, The Villas Bali Hotel and Spa, one of lodging firm atKuta, Badung, that getting assimilates to outrival by effort a sort also noticestress and industrial relationship in effort increases employee performance.This research was aimed to find out how the influences of stress andindustrial’s relationship and variable which that influential largest for theemployee performance of The Villas Bali Hotel and Spa, Kuta, Badung. Toanswer that, therefore done by research where all employee which is 84 personare made as respondent. Hereafter the data analysis consisting of validity andreliability of research instrument (quitionare), classic assuming test, andmultiple regression analysis (simultant and partial test)Based on analysis result is gotten that stress and industrial's relationshipin simultant and also partially effect, having for significant for employeeperformance of The Villas Bali Hotel and Spa Kuta, Badung. Industrial'srelationship having for greater influence for employee performance of The VillasBali Hotel and Spa Kuta, Badung.
Keywords: stress, industrial' s relationship, performance of employee